2012
DOI: 10.1155/2012/231693
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Mucosal Melanoma of the Head and Neck in the United States

Abstract: Background. While it is established that the incidence of cutaneous melanoma has risen over time in the United States, the incidence trend for mucosal melanoma of the head and neck (MMHN) is unknown. Methods. We used the Surveillance, Epidemiology, and End Results (SEER) database to determine incidence trends for MMHN from 1987 to 2009 in the United States. We determined annual percent change (APC) by weighted least squares and joinpoint regression analysis. Results. MMHN incidence increased from 1987 to 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 25 publications
4
52
0
5
Order By: Relevance
“…Our results are consistent with a Dutch epidemiological study from 2010 with 261 cases of MMHN obtained in the period 1989-2006, which found no significant changes in the incidence of MMHN over time [16]. Two other recent studies, a Swedish study from 2013 [5] and an American study from 2012 [2], showed a significant increase in incidence for sinonasal MM during the study periods, which were 1960-2000 with 186 sinonasal MM cases and 1987-2009 with 452 MMHN cases, respectively. Both studies found a higher incidence of sinonasal MM in women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with a Dutch epidemiological study from 2010 with 261 cases of MMHN obtained in the period 1989-2006, which found no significant changes in the incidence of MMHN over time [16]. Two other recent studies, a Swedish study from 2013 [5] and an American study from 2012 [2], showed a significant increase in incidence for sinonasal MM during the study periods, which were 1960-2000 with 186 sinonasal MM cases and 1987-2009 with 452 MMHN cases, respectively. Both studies found a higher incidence of sinonasal MM in women.…”
Section: Discussionsupporting
confidence: 92%
“…Although melanocytes in the mucosal layers of the head and neck are thought to be histologically identical to melanocytes in the skin [1], the pathogenesis of MM-including MMHN-is unknown. Several etiological agents have been proposed for MMHN, including the use of tobacco and occupational exposure to inhaled carcinogens, but the results are inconclusive [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when comparing incidence data from 1960 and 2010, SCC was still the most frequent tumour followed by SNMM, which was rare in 1960. This increase in the incidence of SNMM has recently been observed in other studies (2,13,14) . The differences in distribu- diagnosis.…”
Section: Discussionsupporting
confidence: 81%
“…2,3 In a study carried out by Marcus, 452 cases of HNMM of the Surveillance, Epidemiology, and End Results (SEER) 9 registry of the United States between 1987 and 2009, were identified. 4 According to this study, the incidence of HNMM in the United States has been rising since 1987. This trend has been driven primarily by increased incidence of nasal cavity melanomas.…”
Section: Introductionmentioning
confidence: 83%